The association between frontal lisping and an anterior open bite, a tongue thrust swallow, the concurrence of an anterior open bite and a tongue thrust swallow and slow diadochokinetic rate - Thompson, Linda (Division of Communication Sciences and Disorders, 2014)
Includes bibliographical references (leaves 97-111).